2018
DOI: 10.30880/ijie.2018.10.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Kenaf Reinforced PLA Composite Thermoforming: A Numerical Simulation

Abstract: Recent manufacturing developments, which focus on optimum product fabrication technique, including thermoforming, are time-consuming and cost-effective. Fundamental studies of the thermoforming process; especially in a uni-directional direction of Kenaf fiber composite, are still in their preliminary stages. Hence, a numerical simulation is performed to minimize experimental conduct. PAM-FORM software is used to model and simulate the thermoforming process, by studying the effects of processing parameters on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The degradation of the kenaf fibers exhibits three stages: Based on the graft, a slight mass loss was observed below 200 °C which may be attributed to evaporation of absorbed moisture. Theoretically, the moisture starts to evaporate at a temperature of 80 °C because it is difficult to totally eliminate the water even though the kenaf was dried in an oven before running the TGA analysis [ 16 , 31 ]. Table 2 shows that treated fibers have less mass loss than untreated kenaf fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of the kenaf fibers exhibits three stages: Based on the graft, a slight mass loss was observed below 200 °C which may be attributed to evaporation of absorbed moisture. Theoretically, the moisture starts to evaporate at a temperature of 80 °C because it is difficult to totally eliminate the water even though the kenaf was dried in an oven before running the TGA analysis [ 16 , 31 ]. Table 2 shows that treated fibers have less mass loss than untreated kenaf fibers.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2, at the temperature range of 60 to 120 • C, the kenaf/PP composites were able to achieve a maximal tensile strength that ranged from 70 to 90 MPa, which is sufficient for automotive parts (e.g., a trunk cover or dashboard) that require a tensile strength of around 30 MPa [2,15]. These findings indicated that kenaf/PP composites are appropriate to be used, given that the applied temperature (60 to 120 • C) was near that of other commercial composite products used in high-temperature applications that can offer better mechanical properties [18]. Furthermore, Figure 2 demonstrates that, as the orientation angle increased from 0 • to 45 • and 90 • , tensile strength dropped dramatically, from~90 to~20 MPa, even though theoretically, the fibers being aligned in one direction within the composite materials should enhance their mechanical properties [7,27].…”
Section: Characterizationmentioning
confidence: 86%
“…Hence, these processes can be implemented elsewhere, for example, in dashboard panels and trunk covers. Prior research exhibited that adapting the compression-molding process aids in developing an aligned kenaf composite [ 18 ]. Thus, it strengthens the mechanical properties of kenaf composites, as its performance can be altered according to manufacturers’ needs.…”
Section: Introductionmentioning
confidence: 99%
“…PLA is considerably studied as a synthetic bioabsorbable polymer for potential applications in bone tissue engineering. The advantages of PLA are its bioresorbability, biocompatibility, biodegradability, versatility and ease of manufacturing [1,5] Though, PLA alone often does not have the mechanical strength required for loading application, lack of ability to integrate with the bone and discharge acidic degradation products that may have adverse effects on the tissue response [6]. Alternatively, some research has reported that pure polymer implants ordered for bone reconstruction were not practical [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are insufficient publications involving injection moulding of PLA/n-HAP nanobiocomposite systems composed of PLA and biogenic n-HAP. Consequently, it would be fascinating and significant to explore the properties of injection molded PLA/n-HAP nanocomposites, which could provide a good groundwork for the fabrication of PLA-based biomedical composite with good inclusive performance [5]. Therefore, injection moulding technology was employed to fabricate PLA/n-HAP nanocomposite in this current research.…”
Section: Introductionmentioning
confidence: 99%